Kejadian Bullying Dengan Perilaku Percobaan Bunuh Diri Pada Remaja: Literature Review - Sutini, Titin (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Bullying is negative behavior by a person or group that is carried out repeatedly and is offensive because there is an imbalance of power between the parties involved, this can make teenagers have suicidal thoughts. Attempted suicide is an individual's direct action directed at himself which, if not stopped, will result in death. The aim of this literature review is to determine the incidence of bullying and attempted suicide in adolescents, involving what factors influence this incident. Methods: The method used in writing this article is a literature review. The literature search process uses the PICO approach, uses 7 English articles by searching through the EBSCOhost, PUBMed, Sciencedirect and Proquest databases. in three data sources, namely Google Scholar, PubMed, and EbscoHost. Results: The results of this investigation show that the risk factors and protective factors for ideation, suicide attempts, gender differences in bullying victimization, the independent relationship of bullying with an increased risk of suicidal ideation among adolescents, factors that are related to suicidal behavior, and the risk and protective factors that moderating the relationship between three types of bullying victimization are some of the causes of suicide in adolescents. Conclusion: That there are many factors that influence the incidence of suicide and bullying behavior in adolescents.